MANAGEMENT OF SEA RESOURCES BASED ON LOCAL WISDOMS IN CONSERVATION OF ISLAND KEI IN MALUKU TENGGARA REGENCY - Natelda R. Timisela; Hellen Nanlohy; Ignatia Dyahapsari (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
The aim of research to determine the potential and use of marine resources, describe the values of local wisdom that have relevance to the management of marine resources, and describe forms of marine resource management. The research method used is survey method, by conducting in-depth interviews and focus group discussions. The research location is located in Kei Island conservation area, Pulau-Pulau and the surrounding waters, Southeast Maluku Regency. Data were analyzed descriptively qualitative by describing all variables examined clearly and accurately. The results showed that the Kei Islands have incredible potential of the region, has the potential of fisheries and aquaculture is quite high and the fishery management area of strategic importance. The management of the area with the local wisdom approach of the community is carried out for generations, namely the culture of the sea and the culture of eating together. Local wisdom that is run so far strongly supports the determination of watershed conservation area. The forms of marine resource management in the conservation area is still governed by the rules verbally as is customary informal. The threat to the conservation of marine resources need to be aware through an integrated supervision sustainability of marine resources in order to remain protected, conservation and sustainable development. Keywords management, conservation area, local wisdom, community.